Green Synthesis of Silver Nanoparticles Using Paullinia cupana Kunth Leaf Extract Collected in Different Seasons: Biological Studies and Catalytic Properties - Lima, Alan Kelbis Oliveira; Vieira, Ítalo Rennan Sousa; dos Santos Souza, Lucas Marcelino; Florêncio, Isadora; da Silva, Ingrid Gracielle Martins; Tavares, Alberto Gomes [UNESP]; Machado, Yasmin Alves Aires; dos Santos, Lucas Carvalho; Taube, Paulo Sérgio; Nakazato, Gerson; Espindola, Laila Salmen; Albernaz, Lorena Carneiro; et al. (MDPI, 2025)
Background:Paullinia cupana Kunth, popularly known as guarana, a native Amazonian shrub cultivated by the Sateré-Mawé ethnic group, has been used in traditional medicine for various purposes, including stimulant and therapeutic actions, due to its chemical composition, which is rich in bioactive compounds. This study explored the reductive potential of guarana with nanobiotechnology and aimed to synthesize silver nanoparticles (AgNPs) using the aqueous extract of leaves collected during the dry and rainy seasons, assessing their biological and catalytic activities. Methods: The AgNPs were synthesized in a water bath at 70 °C for three hours and then characterized using techniques such as UV-Vis spectroscopy, DLS, zeta potential, MET, NTA, and EDX and had their effects on various biological systems assessed in vitro, as well as in catalytic tests aimed at indicating the probable influence of the time when the plant material was collected on the properties of the nanostructures. Results: The AgNPs had an average diameter between 39.33 and 126.2 nm, spherical morphology, absorption bands between 410 and 450 nm, and high colloidal stability over two years. The biological results showed antibacterial activity against all the species tested, as well as remarkable antioxidant action against DPPH and ABTS free radicals, in the same way as the aqueous leaf extracts of P. cupana, in addition to cytotoxic properties against cancerous (A431 and A549) and non-cancerous (HaCaT and HNTMC) cells. The AgNPs were active against promastigote forms of Leishmania (Leishmania) amazonensis while not affecting the viability of macrophages, and from the LC50 and LC90 values, the AgNPs were more effective than the metal salt solution in controlling Aedes aegypti larvae and pupae. We also reported that the catalytic degradation of the organic dyes methylene blue (MB) and methyl orange (MO) by AgNPs was over 90% after 40 or 14 min, respectively. Conclusions: Thus, our results support the potential of seasonal extracts of guarana leaves to produce AgNPs with diverse application possibilities for the health, industrial, and environmental sectors.